The relationship between population and interest rates toward housing price in Selangor, Johor and Pulau Pinang / Rialianareenawaty Raub - Raub, Rialianareenawaty (2007)
This study is conducted to examine the general relationship between population and interest rates toward housing price over more recent period from 1999 to 2005. This study comprises three locations in Malaysia, which are Johor, Selangor and Pulau Pinang. Methodology used for the purpose of this research is multiple regression models. House price may go up for many reasons. Some are the result of change in demand such as rising in population and interest rates. Regional population changes are a key factor when explaining house price performance. More people move to an area, the higher the house prices will rise. The mortgage interest rate is one such variable with a global impact, especially in the context of housing market transactions. The movements of interest rates may occasionally give misleading information about the direction and extent of movements in housing prices beyond rational limits. Interest rates are likely to have an important impact on housing prices and transaction volume. According to my research populations appear strongly significant relationship in explaining the housing price level. While interest rates result show no significant relationship with housing prices. Since the interest rates are not significant this regression is acceptable because the adjusted coefficient of determination R-Square (R2) is equal near to l. It indicates that housing price is strongly explained by population and interest rates.